Assessment of satisfaction level of edentulous patients rehabilitated with implant-supported prostheses - de Souza, Fernando Isquierdo [UNESP]; Costa, Alessandro de Souza; Pereira, Rodrigo dos Santos [UNESP]; dos Santos, Paulo Henrique [UNESP]; de Brito, Rui Barbosa; Rocha, Eduardo Passos [UNESP] (Quintessence Publishing, 2016)
Purpose: Edentulism usually leads to esthetic, functional, and emotional discomfort resulting in a loss of self-esteem and a decrease of the patient's quality of life. Dental implants provide new possibilities to ensure the comfort and efficacy of prosthetic rehabilitation. The aim of this study was to evaluate the satisfaction level of patients rehabilitated using the Brånemark protocol or overdenture implant-supported prostheses. Materials and Methods: Fifty-two patients were rehabilitated using the Brånemark protocol and 23 using overdenture prostheses. Then, an adapted oral health-related quality of life questionnaire was administered in addition to a clinical exam to determine the condition of the dental implants and prostheses. The results for treatment expectation, understanding of the type of treatment, phonetic function, chewing comfort, pain, and self-esteem improvement were analyzed with Fisher exact test (P ≤ .05). Results: Both treatments presented satisfaction of above 87%, with no statistical difference between them. Eighty-two percent of patients treated with overdenture prostheses and 80.8% of those treated with the Brånemark protocol had no complaint of pain (P = .087). Conclusion: The treatments analyzed in this study were highly satisfactory with regard to functional and esthetic factors, resulting in an increase in self-esteem and quality of life. The psychological factor is a complex variable in patient satisfaction that directly influences quality of life. Considering the desires of patients in choosing the type of prosthesis is critical to treatment success.
Keywords: Dental implants; Edentulous mouth; Implant-supported denture; Overdenture; Patient satisfaction